233k views
2 votes
A equals 2 pi r squared + 2 pi r h what is h equal to​

1 Answer

2 votes

Answer:


h=(a)/(2\pi r)-r

Explanation:

The equation in this problem is:


a=2\pi r^2 + 2\pi r h

We want to find an expression for h. Let's start by subtracting
2\pi r^2 from both sides, we get:


a-2\pi r^2 = 2\pi rh

Now we divide both sides by
2\pi r, and we get:


(a-2\pi r^2)/(2\pi r) = h

And by simplifying,


h=(a)/(2\pi r)-r

User Jeffrey Godwyll
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.